Regulation of transmembrane water flow in Avena sativa seedlings under drough conditions - T.I. Puzina; I.Yu. Makeeva (Известия высших учебных заведений. Поволжский регион: Естественные науки, 2023)
Background. The permeability of biological membranes for water is determined both by the state of the lipid bilayer and the water channels formed by a highly conserved group of proteins, aquaporins. Aquaporins significantly reduce the activation energy of transmembrane water transfer. The water permeability of aquaporins is determined either by their amount in the membrane, or by the “open” or “closed” state of the water channel. It has been shown that the regulation of water transport through the water channels of membranes can occur both at the transcriptional and post-translational levels. It is known that aquaporin genes are induced under the action of hormones or under stress. Posttranslational events include phosphorylation, glycosylation, export of vesicles with aquaporins, and protein-protein interactions. At the same time, no information was found on the participation of antioxidants in the regulation of the transmembrane water flow through aquaporins under stress conditions. At the same time, the regulation of membrane permeability for various substances, including water, plays an important role in the adaptation of organisms to various types of stress. The aim of the study was to study the effect of the antioxidant caffeic acid on the transport of water through aquaporins and the water-holding capacity of oat seedlings under drought conditions. Materials and methods. The object of the study was 21-day-old seedlings of spring oats (Avena sativa) cv. Plants were grown in containers with soil “Universalnaya dlya rassady” under laboratory conditions. Variants of the experiment included: spraying 10-day-old seedlings with a 0.1 mM solution of caffeic acid (Sigma, USA), control seedlings were sprayed with water. Drought was created by stopping watering of 15-day-old seedlings for 6 days. It is known that in the early stages of growth, oat plants are very sensitive to water supply and therefore do not tolerate drought well. Water transport through aquaporins was determined by the inhibitory method using a 100 μM solution of mercury chloride, which, interacting with cysteine, sterically blocks the passage of water through the channel or changes the conformation of aquaporins. The openness (activity) of water channels was determined using 100 μM sodium fluoride solution, which inhibits the activity of phosphatase, which dephosphorylates aquaporins. The water-retaining capacity of the leaves was characterized by the amount of water lost to a hypertonic solution. Water loss was expressed as a percentage of the initial wet weight. The wet weight of the leaves of 21-day-old oat seedlings was determined by weighing on an electronic balance VST-600/10 (Russia). Results.The results of the study showed that caffeic acid, which is a phenolic compound, under optimal water supply conditions, increased the flow of water through aquaporins by 1.4 times. Under conditions of a 6-day drought, water transport through aquaporins in oat seedlings decreased by 25%. Under these conditions, caffeic acid not only restored the flow of water through the aquaporins, but also increased it. Blocking of phosphatase activity with 100 μM NaF solution under optimal water supply revealed a significant (by 56%) activation of water inflow through aquaporins in the control variant, which indicates the “opening” of water channels. Under these conditions, caffeic acid increased the flow of water through aquaporins by 40% versus control. Under drought conditions, aquaporins were phosphorylated to a lesser extent compared to optimal conditions, as evidenced by a decrease (by 1.7 times) in the activation of water inflow under the influence of sodium fluoride. Caffeic acid significantly contributed to the "opening" of water channels under these conditions (2.2 times). A 6-day drought increased the waterretaining capacity of oat seedling leaves by 1.3 times, as evidenced by lower water loss under these conditions. Caffeic acid contributed to an increase in water-retaining capacity, moreover, to a greater extent under stressful conditions (by 30% versus 20% in control). A 23% decrease in the wet weight of the leaves of seedlings grown under drought conditions was revealed. Caffeic acid stimulated growth, and under stress conditions, seedling mass reached the control variant with optimal water supply. Conclusions.Thus, the study indicates the participation of caffeic acid in the regulation of the transmembrane water flow through aquaporins, the water-retaining capacity of cells both under optimal water supply conditions and during drought. This may be due to its antioxidant function and the effect on the content of phytohormones of auxins, which was shown by us in previous studies.